High-sensitivity cardiac troponin T delta concentration after repeat pulmonary vein isolation - Zeljkovic, Ivan (Array, 2019)
Difference between high-sensitivity cardiac troponin T concentrations (hs-cTnT) before and after ablation procedure (delta concentration) reflects the amount of myocardial injury. The aim of the study was to investigate hs-cTnT prognostic power for predicting atrial fibrillation (AF) recurrence after repeat pulmonary vein isolation (PVI) procedure.Materials and methods: Consecutive patients with paroxysmal AF undergoing repeat PVI using a focal radiofrequency catheter were included in the study. Hs-cTnT was measured before and 18-24 hours after the procedure. Standardized 3, 6 and 12-month follow-up was performed. Cox-regression analysis was used to identify predictors of AF recurrence.Results: A total of 105 patients undergoing repeat PVI were analysed (24% female, median age 61 years). Median (interquartile range) hs-cTnT delta after repeat PVI was 283 (127 - 489) ng/L. After a median follow-up of 12 months, AF recurred in 24 (23%) patients. A weak linear relationship between the total radiofrequency energy delivery time and delta hs-cTnT was observed (Pearson R2 = 0.31, P = 0.030). Delta Hs-cTnT was not identified as a significant long-term predictor of AF recurrence after repeated PVI (P = 0.920).Conclusion: This was the first study evaluating the prognostic power of delta hs-cTnT in predicting AF recurrence after repeat PVI. Delta hs-cTnTdoes not predict AF recurrence after repeat PVI procedures. Systematic measurement of hs-cTnT after repeat PVI does not add information relevant to outcome.